Heat transfer and exergy loss in a concentric heat exchanger with snail entrance - Durmus, A (Pergamon-Elsevier Science Ltd, 2002)
It would be misleading to consider only cost aspect of the design of a heat exchanger. High service costs increase total costs during the service life of heat exchanger. Therefore, energy saving is the most important parameter in the heat exchange design. The most effective way in energy saving by increasing the efficiency in a heat exchanger is to increase the heat transfer coefficients in cold and warm fluid sides with respect to present case. This comes true with one or a few of active or passive ways. In this study, in order to increase heat transfer in concentric double-pipe heat exchangers by passive method, snail which is mounted at inlet of the inner pipe and assumed as a swirl generator was used. (C) 2002 Elsevier Science Ltd.